2021
DOI: 10.3390/genes12060817
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Organization of the Drosophila melanogaster Genome

Abstract: Interphase chromatin, despite its appearance, is a highly organized framework of loops and bends. Chromosomes are folded into topologically associating domains, or TADs, and each chromosome and its homolog occupy a distinct territory within the nucleus. In Drosophila, genome organization is exceptional because homologous chromosome pairing is in both germline and somatic tissues, which promote interhomolog interactions such as transvection that can affect gene expression in trans. In this review, we focus on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 158 publications
(193 reference statements)
0
12
0
Order By: Relevance
“…Insulator proteins are classically associated with demarcating the boundaries of chromatin domains in order to block the spreading of repressive chromatin and inhibit enhancer-promoter contacts (Moretti et al 2020). Further studies revealed their roles in mediating long-range interactions between distant genomic sequences, and in the formation of the 3D chromatin structure (Moretti et al 2020; Peterson et al 2021). Moreover, the involvement of insulator proteins in PcG function becomes more and more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Insulator proteins are classically associated with demarcating the boundaries of chromatin domains in order to block the spreading of repressive chromatin and inhibit enhancer-promoter contacts (Moretti et al 2020). Further studies revealed their roles in mediating long-range interactions between distant genomic sequences, and in the formation of the 3D chromatin structure (Moretti et al 2020; Peterson et al 2021). Moreover, the involvement of insulator proteins in PcG function becomes more and more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Insulator elements organize the genome into chromatin loops 5 that are involved in the formation of topologically associating domains, TADs [29][30][31] . In mammals, CTCF-dependent loop formation requires ATP-driven motor activity of SMC complex cohesin 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Insulator elements organize the genome into chromatin loops (Gerasimova et al, 1995) that are involved in the formation of topologically associating domains, TADs (Peterson, Samuelson, & Hanlon, 2021; Rowley et al, 2017; Szabo, Bantignies, & Cavalli, 2019). In mammals, CTCF-dependent loop formation requires ATP-driven motor activity of SMC complex cohesin (Davidson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Scale bars: 20 μm. b Volume quantification of Raeppli clones in the VNC at ALH0 (n = 7), ALH24 (n = 25), ALH48 (n = 21),ALH72 (n = 32) and ALH96 (n = 30 intimately joined from end to end 46,47 . Moreover, multiple copies of homologous chromosome also appear to be paired along their length in extreme case of endoreplication (polytene chromosomes).…”
Section: Cg Undergo Both Endoreplicative and Mitotic Eventsmentioning
confidence: 99%